Analisis Kepuasan Pegawai Dalam Menggunakan Aplikasi ePAU di Kantor SKK Migas Perwakilan Sumbagsel - nining ariati; sukesih aprilia; Faradillah Faradillah (Universitas Katolik Musi Charitas, 2022)
ePau is an application developed by SKK Migas as a reference for the management of the official document management within SKK Migas. This research is to measure how satisfied SKK Migas employees are with the ePau application. The method used in this study is End User Computing Satisfaction (EUCS) which consists of five factors, namely: content (content), accuracy (accuracy), format (form), ease of use (ease of use) and timeliness (time). Through this ePau application, you can create, improve, and improve management within the SKK Migas environment, starting from managing incoming and outgoing letters to storing letters in the application. The results to be obtained are to determine the level of satisfaction of SKK Migas representatives from South Sumatra on the performance of the ePau application.